Defining the Structure-Function Relationships of Bluetongue Virus Helicase Protein VP6 - Kar, Alak Kanti (American Society for Microbiology, 2003)
The VP6 protein of bluetongue virus possesses a number of activities, including nucleoside triphosphatase, RNA binding, and helicase activity (N. Stauber, J. Martinez-Costas, G. Sutton, K. Monastyrskaya, and P. Roy, J. Virol. 71:7220-7226, 1997). Although the enzymatic functions of the protein have been documented, a detailed structure and function study has not been completed and the oligomeric form of the protein in solution has not been described. In this study, we have characterized VP6 activity by creating site-directed mutations in the putative functional helicase domains. Mutant proteins were expressed at high levels in an insect cell by using recombinant baculoviruses purified and analyzed for ATP binding, ATP hydrolysis, and RNA unwinding activities. UV cross-linking experiments indicated that the lysine residue in the conserved motif AXXGXGK(110)V is directly involved in ATP binding, whereas mutant R(205)Q in the arginine-rich motif ER(205)XGRXXR bound ATP at a level comparable to that of the wild-type protein. The RNA binding activity was drastically altered in the R(205)Q mutant and was also affected in the K(110)N mutant. Helicase activity was altered in both mutants. The mutation E(157)N in the DEXX sequence, presumed to act as a Walker B motif, showed an intermediate activity, implying that this motif does not play a crucial role in VP6 function. Purified protein demonstrated stable oligomers with a ring-like morphology in the presence of nucleic acids similar to those shown by other helicases. Gel filtration chromatography, native gel electrophoresis, and glycerol gradient analysis clearly indicated multiple oligomeric forms of VP6.